Beyond the consultation room: Proposals to approach health promotion in primary care according to health-care users, key community informants and primary care centre workers. - Berenguera, Anna; Pons ‐ Vigués, Mariona; Moreno ‐ Peral, Patricia; March, Sebastià; Ripoll, Joana; Rubio ‐ Valera, Maria; Pombo ‐ Ramos, Haizea; Asensio ‐ Martínez, Angela; Bolaños ‐ Gallardo, Eva; Martínez ‐ Carazo, Catalina; Maderuelo ‐ Fernández, José Ángel; Martínez ‐ Andrés, Maria; et al. (Health Expectations, 2017)
Background Primary health care ( PHC) is the ideal setting to provide integrated services centred on the person and to implement health promotion ( HP) activities. Objective To identify proposals to approach HP in the context of primary care according to health-care users aged 45-75 years, key community informants and primary care centre ( PCC) workers. Methods Descriptive-interpretive qualitative research with 276 participants from 14 PCC of seven Spanish regions. A theoretical sampling was used for selection. A total of 25 discussion groups, two triangular groups and 30 semi-structured interviews were carried out. A thematic interpretive contents analysis was carried out. Results Participants consider that HP is not solely a matter for the health sector and they emphasize intersectoral collaboration. They believe that it is important to strengthen community initiatives and to create a healthy social environment that encourages greater responsibility and participation of health-care users in decisions regarding their own health and better management of public services and resources. HP, care in the community and demedicalization should be priorities for PHC. Participants propose organizational changes in the PCC to improve HP. PCC workers are aware that HP falls within the scope of their responsibilities and propose to increase their training, motivation, competences and knowledge of the social environment. Informants emphasize that HP should be person-centred approach and empathic communication. HP activities should be appealing, ludic and of proven effectiveness. Conclusions According to a socio-ecological and intersectoral model, PHC services must get actively involved in HP together with community and through outreach interventions.